2001
DOI: 10.1021/jo015897c
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Factors in the Synthesis of Cucurbituril and Its Homologues

Abstract: The acid-catalyzed synthesis of cucurbit[n]urils from formaldehyde and glycoluril is poorly understood. In this paper, we examine a wide range of reaction conditions that include the effects of acid type, acid concentration, reactant concentrations, and temperature to both probe the mechanism and optimize the yields of isolated cucurbit[n]urils, where n = 5-10. A mechanism for the formation of these cucurbit[n]urils is presented. Individual cucurbit[n]urils were unambiguously identified in reaction mixtures us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
1,175
1
18

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 969 publications
(1,212 citation statements)
references
References 23 publications
18
1,175
1
18
Order By: Relevance
“…Q [9] or Q [10]. 40 Similar reductions in the distances between Pt-Pt centres were also found for the tri-Pt complexes. Q [7] was shown to encapsulate the hydrolysed form of di-Pt, and based upon the similarity of the chemical shifts of the bound metal complex, it can be concluded that the cucurbituril was positioned in a similar fashion to the Cl form of di-Pt.…”
Section: Discussionsupporting
confidence: 61%
“…Q [9] or Q [10]. 40 Similar reductions in the distances between Pt-Pt centres were also found for the tri-Pt complexes. Q [7] was shown to encapsulate the hydrolysed form of di-Pt, and based upon the similarity of the chemical shifts of the bound metal complex, it can be concluded that the cucurbituril was positioned in a similar fashion to the Cl form of di-Pt.…”
Section: Discussionsupporting
confidence: 61%
“…Cucurbit [7]uril (CB7) was synthesized according to the literature. [76][77][78] Acridine orange (AO), thermolysin (lyophilized powder, 36.5 U/mg) and phosphoramidon were used as received from Sigma-Aldrich.…”
Section: Exo-and Endopeptidase Behaviormentioning
confidence: 99%
“…21,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] The pioneering work of Lehn, Cram, and Pedersen brought host-guest and supramolecular chemistry to the forefront of contemporary science. [44][45][46] The scientific insights gained from fundamental studies of non-covalent interactions have been of practical value in a wide range of applications including chromatographic stationary phases, sequestration of contaminants from solution, and the development of catalysts, chemical sensors, and new drugs.…”
Section: List Of Figuresmentioning
confidence: 99%